ChemInform Abstract: Origin and Location of Electrons and Protons During the Formation of Intermetalloid Clusters [Sm@Ga3‐xH3‐2xBi10+x]3‐ (x = 0, 1). Issue 4 (January 2015) - Weinert, Bastian; Mueller, Fabian; Harms, Klaus; Clerac, Rodolphe; Dehnen, Stefanie
Abstract [K([2.2.2]crypt)]3 [Sm@Ga2HBi11]0.9 [Sm@Ga3H3Bi10] 0.1·en·tol is synthesized from a mixture of [K([2.2.2]crypt)]2[GaBi3]·en and Sm(C5Me4H)3 in en (3 h in the dark) followed by layering with toluene (4 °C, 3 d, 10% yield).